Influence of statistical tools in data journalism in universities - Caballero Cifuentes, Lolo; Quivio Cuno, Richard; Morales Romero, Guillermo; Gutiérrez Guadalupe, Sandra; Barrientos-Báez, Almudena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article arises with the objective of investigating the influence of statistical tools in data journalism, in private universities. The methodology is basic, with a descriptive, correlational-causal design. The sample was probabilistic, made up of 98 students to whom the validated and reliable instruments were applied with expert judgment and the Cronbach Alpha Coefficient. The results show that more than 60% of the total students presented medium levels in the use of statistical tools for data journalism. It was concluded that there is influence with a preponderant link.